Time to go wireless? A 15-year single institution experience of radioisotope occult lesion localisation (ROLL) for impalpable breast lesions. Issue 1 (January 2017) - Hawkins, S.C.; Brown, I.; King, P.; El-Gammal, M.; Stepp, K.; Widdison, S.; Barta, M.; Jackson, N.; English, R.; Ahmad, S.; Drew, P.
Abstract: Introduction: Wire guided localisation (WGL) is the standard localisation technique for impalpable breast lesions. Radio-guided occult lesion localisation (ROLL) has been proposed as an alternative. We have been performing ROLL for therapeutic wide local excisions (WLE) and diagnostic excision biopsies (DEB) for the last 15 years. We present the largest reported consecutive series of ROLL excisions to date. Patients and methods: One thousand thirty nine consecutive patients who underwent ROLL for impalpable breast lesions were identified from a prospectively collected database. 673 patients underwent WLE and 366 patients underwent DEB. Data were analysed from proformas completed at the time of the procedure by the radiologist and operating surgeon. These data were supplemented with an analysis of patient electronic records including specimen radiograph and histopathology reports. Results: 99.1% of ROLL WLE revealed histological diagnoses of invasive cancer or DCIS. 98.7% of radiological abnormalities were identified on WLE post-excision radiographs (97.5% following DEB). Complete excision was recorded in 79.0% of the WLE patients following histological evaluation. 31.7% of DEB cases were pathologically upgraded to a malignant diagnosis. The presence of microcalcification, preoperative underestimation of the lesion size and symptomatic referral predisposed to incomplete excision status. Discussion: ROLL is a safe and effective technique to localise impalpable breast lesions. In addition ROLL has potential technical and logistic advantages over WGL.